Two new montane species of Acanthosaura Gray, 1831 (Squamata: Agamidae) from Peninsular Malaysia - Wood Jr., Perry L.; Grismer, Jesse L.; Grismer, L. Lee; Ahmad, Norhayati; Onn, Chan Kin; Bauer, Aaron M. (Zootaxa, 2009)
Two new montane species of the agamid genus Acanthosaura (Gray, 1831) from Peninsular Malaysia are described based on having unique color pattern and scale characteristics. Acanthosaura bintangensis sp. nov. from Bukit Larut, Perak most closely resembles A. titiwangsaensis sp. nov. from Fraser’s Hill and Cameron Highlands, Pahang but differs from it by having more subdigital lamellae on the fourth finger; the presence of a row of enlarged keeled suborbital scales beginning and terminating with an elliptical keeled scale; by having more scales surrounding the occipital spines; having more spots in the dorsal pattern; and by having a black gular region with a yellow medial stripe. Both species closely resemble A. crucigera but, can be separated from it by having higher numbers of subdigital lamellae on the fourth finger and toe; higher numbers of trasverse scales in the canthus rostralis-supraorbital ridge; higher numbers of scales bordering the rostral scale, and lower numbers of scales between the fifth canthals. The discovery of a two new agamid lizards from montane forests in well-known areas of Peninsular Malaysia underscores the importance of continued field work in these regions.